Posterior cruciate ligament avulsion fixation: A minimally invasive retrograde fixation by a single cannulated screw - Madadi, Firoozeh; Madadi, Firooz; Aslezaker, Maryam (Researcher Bulletin of Medical Sciences, 2021)
The optimal surgical treatment of isolated tibial avulsion fractures of the Posterior Cruciate Ligament remains controversial. The purpose of this study was to evaluate the results of an arthroscopic technique using two ordinary portals and an incision to stabilize an avulsed fragment. Five patients were treated and followed up for 4 years. The mean score measured by KT-2000 was 9.2 mm preoperatively, 4.6 mm a year (P<0.042) and 3.8 mm 4 years postoperatively (p<0.041). This study showed that fixing the PCL avulsion fractures by a cannulated screw could improve knee function and stability.